Comparison of illustrative handouts and self-drawing on learning outcomes from anatomy lectures - Suresh Narayanan; Nachiket Shankar (Wolters Kluwer Medknow Publications, 2021)
Background: Illustrative handouts and self-drawing have been shown to improve learning outcomes from lectures. The objective of this study was to compare the test scores among students taught using these two methods in anatomy lectures and to assess the students' perceptions about the same. Methodology: This was a quasi-experimental pre- and post test study done among 1st-year medical undergraduates to evaluate the effectiveness of illustrated handouts. For two of the lectures (Group 1 lectures), students were asked to draw along with the teacher, while for the other two lectures (Group 2 lectures), they were given illustrative handouts and were required to progressively color and label. The multiple-choice questions were administered prior to the lectures and 4 months after completion of the lectures. The paired t-test, Wilcoxon signed-rank test, and Mann-Whitney U-test were used to estimate score differences. Students' perceptions were assessed using a questionnaire. Results: There was a significant improvement in post test scores for both handout and self-drawing sessions. The score improvement was significantly higher for the handout session when compared to the self-drawing session. No significant gender differences were noted. More than 80% of the students had positive opinions about all aspects of the handouts that were assessed. Conclusion: Supplementing lectures with illustrative handouts resulted in higher knowledge retention when compared to self-drawing. Students felt that illustrated handouts facilitated their learning from lectures.